Would a morphomolecular approach help in defining pseudosarcomatous myofibroblastic proliferations? A study of a heart polypoid lesion. Issue 4 (3rd December 2008) - Nemolato, S; Dettori, T; Caria, P; Frau, D V; Faa, G; Vanni, R
Abstract : Many cardiac neoplasms lack pathognomonic clinical features, and this leads to controversial interpretations. As genomic changes may correlate with these malignancies and possibly aid in diagnosis, fluorescence in situ hybridisation (FISH) was used to study a polypoid lesion found incidentally at autopsy on the septal wall of the left ventricle of a 75-year-old man who had died from a heart attack. Histology and immunohistochemistry disclosed atypical stromal cells with irregular voluminous nuclei positive for vimentin and smooth muscle actin; these cells were reminiscent of those previously reported in a subset of nasal polyps showing aneuploidy. The scarce lymphoplasmocytic infiltrate hindering the diagnosis of inflammatory myofibroblastic tumours (IMT), and the presence of atypical cells, prompted the use of FISH: lack of ALK gene rearrangement and aneuploidy were observed in the irregular nuclei, supporting the diagnosis of a pseudosarcomatous myofibroblastic proliferation (PMP). These results stress that IMT and PMP may represent variants within a spectrum of myofibroblastic proliferations/tumours.